Rehabilitation of Buildings and Knowledge Management: Project HKNOW - Alfredo Soeiro (2010)
The project HKNOW was the first project of 7th Framework Program to be approved in 2008.The title is "Advanced Infrastructure for Knowledge Based Services for Restoring Buildings". It makes part of the Theme 4 - NMP - "Nanosciences, Nanotechnologies, Materials and new Production Technologies". Is it in sub-program Project Collaboration Aimed at Small and Medium Enterprises (SMEs). It has a total funding of the European Commission about 1.9 M and a cost of about 2.6 M . Has fifteen partners from five countries: Portugal, Italy, Germany, France and Spain. The partners in Portugal are 3M2P, INESC, FEUP, STB and Vortal. The project is due to the increasing number of complex works of rehabilitation of buildings that require rapid and systematic access to specific knowledge of such operations. A promising approach to facilitate such access is by providing SMEs in building rehabilitation the proper knowledge through collaborative business networks formed by these companies and partners to research and development (R&D). These innovative solutions for these communities SME-R&D is intended to create and reuse knowledge across a common work and ensure a bi-directional flow between the two sectors. This work provides: (a) provision for community learning the fundamental knowledge and the organization of tacit knowledge of SMEs and (b) closer business collaboration between SMEs and R&D. The intention is also to ensure greater efficiency in the dissemination of fundamental knowledge to create a delivery service with an added value to potential users. The project plans to develop solutions based on information technology and communication that are satisfactory for SMEs which include (1) knowledge that is innovative and competitive and related training through the provision of services and (2) support for implementation of new forms of collaboration SME-R&D through networking.